Investment and Innovative Principles of Regenerative Properties Activation of Fauna and Flora in the Carpathian Macro-Region - Shchury, М. V.; Vynnychuk, О. M. (Statistics of Ukraine, 2017)
There is an urgency and the need for the introduction of radically new principles for the formation of regenerative properties of fauna and flora. It is noted that the basis, the foundation of life on earth, as an organic and inorganic world, is the natural-resource sphere. Reproductive process in the world of plants and animals depends on how the society will be able to assure conservation, applying and protection of natural areas. Now in Ukraine in general and in the Carpathian macroregion in particular depopulation processes are intensified, and regenerative properties of flora and fauna are reduced. First of all it concerns excessive felling of the forest, drying of forest wood, the disappearance and death of many species of animals, increase their number entered in the Red Book. Essentially, society has disturbed the balance of natural resources which is one of the reasons for the intensification of cataclysms in the plant and animal world. Authors of the article have a need to radically change the attitude of human to nature. Foremost it concerns people whose activities relate to the resources of nature: businessmen, pro-government and entrepreneurial structures, local authorities and the public. It is proposed to introduce in Ukraine a European format for solving problems of use, conservation, protection of flora and fauna. At the heart of its implementation, investment and innovation principles of the organization of the natural reproduction process are recommended, which, unlike the current ones, make chaotic, unsystematic, barbarous use and exploitation of biodiversity impossible. The article states that in our country, pro-government structures and the public underestimate the innovative model of development, which is a key factor in the organization of the reproductive process in many EU countries. Requests for science in Ukraine, especially when it comes to investing in the needs of the natural resource sector, are constantly ignored. Science degrades, as convincingly testifies to permanent underfunding and the closure of research institutes by adequate state structures. This explains why in Ukraine, to date, there are no constructive, inexhaustible, balanced principles of exploitation, use, preservation, improvement and modernly organized protection of the flora and fauna, the restoration of its regenerative properties. The authors suggest developing in our country a new model of relations between people - a biocenose sphere, which should be based on the latest achievements of science and technology It is also suggested that the formation of scientific institutes by scientists, which would professionally, with the help of knowledge, provide protection and population of flora and fauna. An important component of the implementation of new principles, in connection with the reproduction of biocenosis, and the provision of a balance in the natural resource area, is adequate state financing, which would be planned, purposeful and sufficient. Investing in the needs of nature should provide the state as a guarantor for the conservation, protection and provision of a population of flora and fauna for the needs of all citizens of the country